Implicit and explicit sense of agency in individuals with obsessive-compulsive tendencies - Schmidt, Stefan; Wagner, Gerd (Frontiers in Psychology, 2025)
IntroductionThe sense of agency (SoA), or the perception of control over one’s actions and their outcomes, has been proposed to be attenuated in individuals with obsessive–compulsive disorder (OCD) and obsessive–compulsive (OC) tendencies. According to the Sense of Agency and Seeking Proxies for Internal States (SPIS) model, individuals with higher OC tendencies (HOC) may exhibit an altered SoA characterized by diminished tone binding but heightened action binding compared to individuals with lower OC tendencies (LOC).MethodsTo investigate this, 29 healthy participants completed a temporal binding task to measure implicit SoA, alongside self-report measures assessing OC symptoms, anxiety, depression, and explicit SoA. Participants were divided into HOC and LOC tendency groups based on median OCI-R scores. Group comparisons and regression analyses were conducted to examine associations between SoA measures and clinical traits.ResultsSignificant action and tone binding effects were observed across the entire sample, indicating a robust implicit SoA. Contrary to our hypotheses, no significant differences in action or tone binding effects were found between HOC and LOC groups, suggesting a preserved implicit SoA in individuals with higher OC tendencies. Regression analyses revealed that trait anxiety, rather than OC symptom severity, significantly predicted tone binding in the whole sample, indicating an attenuated SoA with increasing trait anxiety levels. Within the HOC group, OC symptom severity significantly predicted tone binding, challenging the SPIS model’s assumption that individuals with high OC tendencies would exhibit diminished tone binding effects. Despite preserved implicit SoA, explicit measures revealed significant group differences, with HOC individuals reporting a lower global SoA.DiscussionThese findings suggest that while implicit, sensorimotor aspects of SoA remain intact in individuals with OC tendencies, alterations emerge at the explicit, cognitive reflective level. This dissociation may reflect compensatory control processes or cognitive biases rather than primary deficits in action–outcome processing. Our findings underscore the need for further research in clinical OCD populations to disentangle the effects of OC symptom severity and subtype on SoA. These insights contribute to a nuanced understanding of agency distortions in compulsive behavior.